Seed germination of yellow passion fruit genotypes - Alexandre, Rodrigo Sobreira; Wagner Júnior, Américo; Negreiros, Jacson Rondinelli da Silva; Parizzotto, Alexandre; Bruckner, Claudio Horst (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this work was to evaluate the germination of seeds of 22 half-sib progenies and two cultivars of Passiflora edulis Sims f. flavicarpa Degener and submit 6 of these genotypes to different times of soak. Two experiments were carried out. The first experiment was set up on an entirely randomized design, with four repetitions, and each genotype was considered as a treatment. In the second experiment, the same experimental design was used, in a factorial 6x4 (genotype x time of soak), with four repetitions. In both experiments, each group of 50 seeds was considered as an experimental unit. In the first experiment, after 28 days, germination percentage and emergency speed were evaluated. After 45 days of survival the percentage, total plantlets and root length, plantlets height, number of leaves and total dry mass of plantlets were evaluated. In the second experiment, after 28 days, the same variables from the first experiment were evaluated, except survival percentage and number of leaves. The seed germination percentage and the emergency speed are not influenced by the different times of soak, but there is effect of plant genotype, indicating that these characteristics can be used for selection in genetic improvement.